Crosstalk Between Liver Macrophages and Surrounding Cells in Nonalcoholic Steatohepatitis - Li, Haiou; Zhou, Yunjiao; Wang, Haizhou; Zhang, Meng; Qiu, Peishan; Zhang, Mengna; Zhang, Ruike; Zhao, Qiu; Liu, Jing (Frontiers in Immunology, 2020)
Nonalcoholic steatohepatitis (NASH), the advanced stage of nonalcoholic fatty liver disease (NAFLD), is emerging as a leading cause of progressive liver fibrosis and end-stage liver disease. Liver macrophages, mainly composed of Kupffer cells (KCs) and monocyte-derived macrophages (MoMFs), play a vital role in NASH progression and regression. Recent advances suggest that cell-cell communication is a fundamental feature of hepatic microenvironment. The reprogramming of cell-cell signaling between macrophages and surrounding cells contributes to the pathogenesis of NASH. In this review, we summarize the current knowledge of NASH regarding the composition of liver macrophages and their communication with surrounding cells, which are composed of hepatocytes, hepatic stellate cells (HSCs), liver sinusoidal endothelial cells (LSECs) and other immune cells. We also discuss the potential therapeutic strategies based on the level of macrophages.